THE ROLE OF ADULTS’ PERSEPTION ABOUT LEARNING ABILITY IN PARTICIPATE IN EDUCATIONAL PROGRAMS AND TRAINING COURSES (EDUCATION IN THE 21ST CENTURY, 2023)
One of the factors that has a major effect on motivating a person is the person's perception of his abilities and capabilities or the so-called self-efficacy. According to theories of self-efficacy and the force field, adults often feel insecure and uncomfortable when they make direct contact with the world today because of dramatic changes and the possibility of not being able to adapt to them. In such a situation, their self-image is shaken and they lose their self-confidence. Insecurity and feelings of inadequacy cause them to lose their motivation and desire to learn. Unfortunately, most adults have a negative attitude towards adults' ability to learn. While human beings at any age have the ability to learn. Adults, like other human beings, have the ability to learn and use new technologies.Purpose of the article: To study the peculiarities of adult learning, especially the barriers to participation in educational programs, the impact of adult's perception of personal potential and learning ability on educational motivation and aspiration.The scientific novelty of the research: The study comprehensively analyzes the issue of adult education in Iran. The article substantiates the research provision that adults' perception of their own abilities has a significant impact on the learning process, and this plays a decisive role in adults’ learning motivations and the involving in educational programs and training courses.
Keywords: Keywords: Adult education, learning ability, learning motivation, educational programs and training courses, adults’ perception, self-efficacy theory, force field theory.